Work climate and Performance Evaluation to Area Chiefs in MINSA Hospitals, Arequipa Region, 2017 - Giselle Milagros Alemán Espinoza (2019)
The objective of the research is to identify the relationship between the organizational climate and performance evaluation. An evaluation of the performance of 360 degrees was made to 55 Heads of Area of Hospitals in the Arequipa Region, 38 men and 17 women, with personnel in charge, with a total of 385 evaluations, applied to their superiors, peers and subordinates with a Questionnaire of Performance Evaluation (own elaboration) and the Sonia Palma CarrilloWork Climate Scale (CL-SPC) was used to measure the work climate. The results obtained by the statistical analysis show that there is no significant relationship between the work environment and work performance, however, if there are significant relationships between the variables and their indicators, separately. An analysis of the results  discussion, conclusions and recommendations are given for the health sector.